Sculptures en montagne - poème dans l'espace. (Passy : Ville de Passy, 1973)
Calder, Alexander ; Cardenas, Agustin ; Casadesus ; Chavignier, Louis ; Delfino, Léonardo ; Etienne-Martin, Henri ; Feraud, Albert ; Gardy-Artigas ; Gastaud, Pierre ; Gilioli, Emile ; Guino ; Guzman ; Hernandez ; Kijno, Ladislas ; Lemesle, Christian ; Miro, Joan ; Mizui, Yasuo ; Otero ; Patkai, Ervin ; Roussil, Robert ; Schultze ; Semser, Charles ; Singer ; van Thienen, Paul
biografie
Sculptures en montagne - poème dans l'espace, Plateau d'Assy, Passy, été 1973
boek